ANALISIS SISTEM PENDINGIN MENGGUNAKAN THERMOSTAT DAN TANPA THERMOSTAT DALAM PENCAPAIAN PANAS MESIN PADA ALAT UJI PRESTASI - Dafit Feriyanto; Sagir Alva; Resista Vikaliana; Asep Setia Kristanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
The ideal working temperature of the engine is about 82 - 93 ⁰C. The engine cooling system is needed to reach and maintain the ideal working temperature of the engine. The engine cooling system is equipped with a thermostat to regulate the flow of cooling water to reach and maintain the temperature. A malfunctioning thermostat will disrupt the cooling system process that led the engine can be overheated. This study aims to analyze the cooling system with and without a thermostat to achieve the ideal working temperature and evaluate the heat distribution on the engine cooling system in the Hyundai Arya diesel engine type D4BB. The research was conducted by various rotations of 800 rpm, 1500 rpm, and 2500 rpm, and the data was collected every 10 minutes. The cooling system without a thermostat can not reach the ideal working temperature of the engine within 10 minutes. Meanwhile, with a thermostat, the ideal working temperature of the engine can be achieved in 9 minutes with an average engine temperature of 86.0 ⁰C at 800 rpm, in 6 minutes with an average engine temperature of 83.5 ⁰C at 1500 rpm, and within 4 minutes with an average engine temperature of 81.7 ⁰C at 2500 rpm. The heat released by the cooling system without a thermostat is less than using a thermostat, with an average of 55.7%. The engine cooling system with a thermostat in the engine cooling system and precise engine temperature control will make the ideal working temperature of the engine more quickly achieved and can be maintained as long as the engine is operated.